2007
DOI: 10.1177/1356336x07072672
|View full text |Cite
|
Sign up to set email alerts
|

Observation of children's physical activity levels in primary school: Is the school an ideal setting for meeting government activity targets?

Abstract: Given the commitment (and funding) by the British government to promote physical activity among all ages, and despite the inevitable political manipulation of physical education (PE) and school sport, there is now an ideal opportunity to focus on primary schools as a key target group for the future. This study determined the physical activity levels of a sample of pre-adolescents over time in a primary school setting. 374 children (5-11 yrs) were directly observed for a total of 30,650 minutes. Continuous obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
28
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
6
28
1
1
Order By: Relevance
“…All the same, the equipment they are talking about has a great variability of possibilities, and it is still in a natural environment. Differences between boys and girls are also shown in other studies (Harten et al, 2008;Haug et al, 2008;Lopes et al, 2006;Nyberg et al, 2009;Waring et al, 2007), which all found a higher level of physical activity among boys. One example is the study made by Harten et al (2008), which found a difference in choices between genders: the boys were more likely to participate in games involving gross motor skills, and the girls were more likely to play in smaller places; boys were competitive and aggressive, and girls were more likely to cooperate and take turns.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…All the same, the equipment they are talking about has a great variability of possibilities, and it is still in a natural environment. Differences between boys and girls are also shown in other studies (Harten et al, 2008;Haug et al, 2008;Lopes et al, 2006;Nyberg et al, 2009;Waring et al, 2007), which all found a higher level of physical activity among boys. One example is the study made by Harten et al (2008), which found a difference in choices between genders: the boys were more likely to participate in games involving gross motor skills, and the girls were more likely to play in smaller places; boys were competitive and aggressive, and girls were more likely to cooperate and take turns.…”
Section: Discussionsupporting
confidence: 67%
“…This need for physical activity will require cortical regulation of the limbic system to reduce the physical activity (Campos et al, 2004), and since boys are often more physically active than girls (Harten, Olds, & Dollman, 2008;Haug, Torsheim, Sallis, & Samdal, 2008;Lopes, Vasques, & de Oliveira Pereira, 2006;Nyberg, Nordenfelt, Ekelund, & Marcus, 2009;Waring, Warburton, & Coy, 2007) this regulation may be a more stressful process for the boys. The sex-based segregation we observe already in childhood is reviewed by Pellegrini (2004).…”
Section: Introductionmentioning
confidence: 98%
“…Increasing their physical activity levels has been identified as particularly important to the long-term impact on public health (Waring, Warburton, & Coy, 2007). Schools have been targeted as the best environments to implement physical activity interventions as they are a primary location to reach the majority of children (Martin & Murtagh, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that less than 20% of children globally [3,4] and less than 50% of children in Ireland [5] meet public health guidelines which recommend that children aged 5-17 years should accumulate at least 60 min of moderate-tovigorous physical activity (MVPA) every day [4]. Increasing the physical activity levels of children has been identified as particularly important given the long-term impact on public health [6]. PA plays an important role in the prevention of overweight and obesity in childhood and adolescence, and reducing the risk of obesity in adulthood [7].…”
Section: Introductionmentioning
confidence: 99%